The impact of pair work on promoting noticing among EFL learners - Sasan Baleghizadeh,; Fatemeh Arab, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This study investigates the effect of pair work on promoting noticing among EFL learners. The participants in this study were 31 Iranian intermediate EFL learners. Tthe participants were first asked to narrate a story in written form. Then, at the second stage, the participants collaborated with a self-selected peer to provide feedback on each other's linguistic problems. Finally, at the third stage, the participants renarrated the story after a week’s interval. While completing the task at the first and second stages, the participants had to make notes on their linguistic problems. Their notes were regarded as the operationalised form of noticing. The results revealed that written output was influential in promoting noticing among the participants. The participants mostly noticed lexical problems at both stages. However, the quality of noticing was low and as a result did not lead to retention and learning at the third stage.